Nutritional Knowledge, Dietary Behaviours, Attitudes, And Body Composition in Elite First-Class Cricketers in Sri Lanka - Nawaz, Farnaz; Wilson, Megan L.; Amarathunga, Hashan; Uggalpaya, Kanishka; McCarthy, Noel; Silva, Tarik De; Aththanayaka, Nimesha Madhumali (JSES : Journal of Sport and Exercise Science, 2026)
Purpose: Nutrition knowledge, attitudes, and behaviours (NKAB) are important determinants of dietary habits and body composition (BC) in athletes.  This study aimed to examine the associations between nutrition knowledge, dietary behaviours, attitudes, and body composition in professional first-class cricketers in Sri Lanka.  This cross-sectional study examined associations between NKAB and BC among 43 of 45 domestically contracted male first-class cricketers in Sri Lanka.   Materials and Methods: NKAB was assessed using the validated Sri Lanka specific Sports Nutrition Knowledge Questionnaire (SLn-SNKQ). BC was measured via the sum of seven-site skinfolds. Descriptive statistics, Pearson’s correlations, and regression analyses explored associations, with significance set at p < 0.05.   Result: Participants displayed moderate nutrition knowledge (mean 8.0 ± 6.1), but no significant associations emerged between NK, behaviours, attitudes, and BC (p > 0.05). Regression analysis showed NKAB collectively did not predict variance in BC (R² = 0.06, p = 0.48).   Conclusion: Higher NK was not associated with more favourable BC, highlighting the influence of contextual and cultural barriers on nutrition practice. The study provides the first dataset on NKAB and BC in Sri Lankan cricketers, emphasizing the need for tailored interventions addressing affordability, accessibility, and cultural norms to bridge the gap between knowledge and practice.